Lord of the flies: pollination of Dracula orchids - Endara, Lorena; Grimaldi, David; Roy, Bitty (Lankesteriana: International Journal on Orchidology, 2010)
The labellum of Dracula orchids looks and smells like mushrooms, and biologists have long hypothesized mushroom mimicry in which mushroom-associated (mycophilous) flies accidentally pollinate these flowers while laying their eggs. In the cloud forest of Ecuador, we observed flower morphology, pollinators and the mechanisms of pollination in two species, Dracula lafleurii Luer & Dalström and D. felix (Luer) Luer. The orchids are visited and pollinated by drosophilid mycophilous flies of the genus Zygothrica, which normally complete part of their life cycles on mushrooms. While these flies court and mate in the flowers, and in the process, pollinate them, they apparently do not lay their eggs in the flowers. The pollination mechanism of Dracula occurs when pollinators’ thoraces are trapped by the incurved flaps of the rostellum which creates an angle between the scutellum and the abdomen for the removal and deposition of the pollinia, a novel feature previously not describe in orchids.